PREVALÊNCIA DE ASPERGILOSE PULMONAR CRÔNICA EM PACIENTES COM TUBERCULOSE - Claudia Elizabeth Volpe Chaves (2021)
Chronic pulmonary aspergillosis (CPA) is a neglected fungal disease, with high morbidity and mortality and the anatomical changes induced by pulmonary tuberculosis (PTB) are the main predisposing factor. Its diagnosis is a challenge and its prevention is little known and probably underestimated by the absence of more accurate diagnostic methods. In addition to microbiological tests, serological tests such as double immunodiffusion on agar gel (DID) or counterimmunoelectrophoresis (CIE) are also used in the routine diagnosis of CPA. More recently, ELISA has been used as an alternative test. The aim of this study was to evaluate the prevalence of CPA in patients with PTB in two health services, in Campo Grande, Mato Grosso do Sul and the accuracy of serological tests for their diagnosis. Two studies were carried out. The first study was a systematic review with the objective of comparing the accuracy of the ELISA test with the reference test (DID and / or CIE) for the diagnosis of CPA. The study was conducted according to “Preferred Reporting Items for Systematic Reviews and Meta-Analyzes” (PRISMA). We conducted the research in the electronic databases MEDLINE (PubMed), EMBASE (Elsevier), LILACS (VHL), Cochrane library, and ISI Web of Science. 14 articles were included with cases of CPA that were submitted to the two tests: ELISA (index test) and DID and / or CIE (reference tests) and that evaluated the accuracy of the tests, but only four could be meta-analyzed. We found no significant difference in sensitivity and specificity in the 4 studies initially analyzed, with a moderate and high heterogeneity, respectively. When we analyzed two studies with commercial tests, the grouped sensitivities were 0.95 (95% CI 0.93–0.97) and 0.49 (95% CI 0.45–0.54) respectively, for the ELISA and DID / CIE test, with no heterogeneity. The second cross-sectional study was conducted with patients with PTB treated at the outpatient clinic of Hospital Universitário Maria Aparecida Pedrossian (HUMAP) or admitted to the Regional Hospital of Mato Grosso do Sul (HRMS) in Campo Grande, Mato Grosso do Sul, between February 2016 and November 2019. To estimate the prevalence of CPA in this population, 193 consecutive eligible patients were included in the study. They underwent clinical, tomographic, sputum and serology tests using the ELISA and DID tests. The overall prevalence of CPA was 10.9%. Having had PTB 4 years or more and having hemoptysis were more frequent in patients with CPA, with odds ratios of 17.54 (1.85-166.67) and 9.61 (2.21-41.67), respectively. Cavitations, pleural thickening and the presence of a fungal ball were the most frequent tomographic changes in CPA. Considering confirmed cases of CPA and 100 healthy blood donors, there was no significant difference in the evaluation of sensitivity and specificity however, the ELISA test performed better than the DID test in the evaluation of the Youden test. The frequency of deaths among patients with CPA was 28.6%. These findings indicate the need for continuous surveillance of CPA in patients with PTB since treatment and throughout life, with clinical, tomographic and serological evaluation, preferably by the ELISA method that demonstrated a better performance in the diagnosis of CPA.